Quality of life in people over 50 HIV+: a comparative study with the general population - Oliveira, Josevânia S.C.; Lima, Flavio Lúcio A.; Saldanha, Ana Alayde W. (Brazilian Journal of Sexually Transmitted Diseases, 2008)
Introduction: the interest in quality of life (QOL) of people aged over 50 HIV + is necessary since they are individuals who have other diseases, which disguise the other symptoms and may cause uncertain or inconclusive diagnosis. Objective: to evaluate the QOL in people over 50 years old HIV + and compare it to the QOL of people from the general population without HIV/aids. Methods: 43 HIV + people participated in a non-probability and accidental study, 62.8% male, with ages ranging from 51 to 78 years old (M =55; SD = 4.6), 43 people without the positivity for HIV, 76.7% female, with ages ranging from 50 to 87 (M = 58.9; SD = 8.65). The instruments used were: Biodemographic questionnaire and Quality of Life Scale for old age (HOQOL-Old). Analyses and multivariate statistics were described by SPSS, version 15.0. Results: the QOV general scoring average was good for the HIV + participants (M = 55.3; SD = 14.6) and the general population (M = 59.3; SD = 17.1). However, in an evaluation by factors, there were low levels of QOL dimensions in “Death and Dying” and “Intimacy” for participants who were HIV + and in the factor “Death and Dying” for participants of the general population. Conclusion: although the general QOL has been satisfactory, aids is still associated to death and suffering, as well as to be imposition of limitations to the experience of intimate relationships for HIV + people, affecting their QOL in that sense.